Corporative culture as an instrument of human resources management - Milushyna, Maryna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The article is devoted to the study of the corporate culture of organizations as a strategic tool in human resource management system. The essence of «corporate culture» concept has been studied and explained from the positions of psychology. We consider the main components of the corporate culture. Corporate culture is represented as a socio-psychological phenomenon, which actually determines the nature of the organization (corporate environment) and, consequently, the content of its activity, creating the appropriate worldview, value-regulatory, as well as behavioral patterns of its functioning. The views of foreign and national scientists concerning the classification of organizational culture typologies are analyzed. The article contains a number of theoretical conclusions, practical tips and advices on the further development of the corporate culture of the organization.

Przedmiotem artykułu jest korporacyjna kultura organizacji jako strategiczne narzędzie w zarządzaniu zasobami ludzkimi. Zbadano treść kategorii „kultury korporacyjnej” z pozycji psychologii. W artykule skoncentrowano uwagę na głównych elementach kultury korporacyjnej. Kultura korporacyjna jest przedstawiona jako fenomen społeczno-psychologiczny, który faktycznie determinuje charakter organizacji (środowisko korporacyjne) i w związku z tym, wyznacza treść jej czynności, tworzy odpowiednie ideologiczne, wartościowe i regulacyjne wzory zachowania w trakcie jej funkcjonowania. Analizuje się poglądy krajowych i zagranicznych naukowców dotyczące klasyfikacji typologii kultury organizacyjnej. Artykuł zawiera wiele wniosków teoretycznych, porad praktycznych i zaleceń dla dalszego rozwoju kultury korporacyjnej.
Keywords: corporate culture; goals; values; behavior; influence; motivation; harmonious development; kultura korporacyjna; cele; wartości; zachowanie; wpływ; motywacja; harmonijny rozwój